The epidemiology of Takayasu arteritis: a hospital-based study from northwestern part of Turkey - DİRESKENELİ, RAFİ HANER (SPRINGER HEIDELBERG, 2016)
Takayasu arteritis (TA) is a chronic, inflammatory large vessel vasculitis that affects aorta and its main branches. We aimed to evaluate the incidence and prevalence of TA in the northwestern part of Turkey. We retrospectively evaluated 23 TA patients followed by our clinic. Clinical features, treatments and responses were recorded. Our hospital is the single tertiary referral center for rheumatic diseases for a mixed rural and urban population of 620,447 people for > 16 years (306,036 males, 314,411 females). Nineteen of the 23 patients were females (82.6 %) and four were males (17.4 %). The annual incidence rate for TA was 0.34/100,000. The overall prevalence of TA in our region was 3.3/100,000 (95 % CI 1.9-4.8) in individuals > 16 years. The most common findings at the time of presentation were blood pressure difference (73 %) and headache (60.4 %). The most common angiographic type was type 1 (12 patients, 52.2 %). Median follow-up period was 48 months (range 10-132). Three (13 %) of the patients had stent replacements to different vascular sites. One patient had an operation for aortic aneurysm, and aortic valve replacement surgery has been made. One patient had renal artery bypass operation. Eleven patients (47.8 %) had recurrency at follow-up period and two patients (8.7 %) died. In northwestern part of Turkey, the annual incidence and prevalence of TA were higher than western population, but similar to East Asian data.
Keywords: Takayasu arteritis; Pulseless disease; Large vessel vasculitis; Epidemiology; PRIMARY SYSTEMIC VASCULITIDES; ANGIOGRAPHIC FINDINGS; CLINICAL-FEATURES; CLASSIFICATION; MANAGEMENT; PROGNOSIS; DISEASE; JAPAN